2020
DOI: 10.1021/acs.jmedchem.0c01498
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of Potent and Brain-Penetrant GPR52 Agonist that Suppresses Psychostimulant Behavior

Abstract: The G protein-coupled receptor 52 (GPR52) is an orphan receptor that is selectively expressed in the striatum and regulates various brain functions through activation of cAMP-dependent pathways. GPR52 has been identified as a promising therapeutic target for central nervous system disorders including schizophrenia and substance use disorders. Here, a series of novel GPR52 agonists were designed, synthesized, and evaluated based on compound 4. Several potent and efficacious GPR52 agonists (12c, 23a, 23d, 23e, 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 33 publications
2
21
0
Order By: Relevance
“…Additional binding affinities for other bromodomain-containing proteins were investigated for compounds 52 and 53 to evaluate their selectivity over other BET members (e.g., BRD3 and BRDT) and non-BET protein (e.g., CBP). For compound 52 , we also conducted non-BET protein panel screening through DiscoverX (Supporting Information, Table S2) and an additional comprehensive screening against more than 40 drug targets from the NIMH psychoactive drug screening program as described in our previous publications , to evaluate the potential off-target effects (Supporting Information, Table S3). Excitingly, this extensive screening endeavor indicated that 52 maintains an overall excellent drug target specificity profile with no or weak binding affinities toward these screened drug targets.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Additional binding affinities for other bromodomain-containing proteins were investigated for compounds 52 and 53 to evaluate their selectivity over other BET members (e.g., BRD3 and BRDT) and non-BET protein (e.g., CBP). For compound 52 , we also conducted non-BET protein panel screening through DiscoverX (Supporting Information, Table S2) and an additional comprehensive screening against more than 40 drug targets from the NIMH psychoactive drug screening program as described in our previous publications , to evaluate the potential off-target effects (Supporting Information, Table S3). Excitingly, this extensive screening endeavor indicated that 52 maintains an overall excellent drug target specificity profile with no or weak binding affinities toward these screened drug targets.…”
Section: Resultsmentioning
confidence: 99%
“…HPLC purity 97.9% (t R = 17.97 min). 1 (53). Compound 53 was synthesized in a yield of 44% as a white solid following the procedure of 52.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
“…GPR52 represents a promising therapeutic target for the treatment of not only HD but also Parkinson's disease (Russell et al, 2021), schizophrenia, and several other psychiatric disorders (Komatsu et al, 2014). For instance, GPR52 agonists are well-known to inhibit D2R signaling and activate D1R/NMDA receptors via intracellular cAMP accumulation, demonstrating antipsychoticlike and procognitive effects in rodents (Setoh et al, 2014;Komatsu, 2015;Nishiyama et al, 2017a;Wang et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Comprehensive transcriptome analysis of non-odorant GPCRs revealed that GPR52 is abundantly expressed in human and rodent striatum and co-localizes with striatal dopamine D2 receptors (Komatsu et al, 2014). Furthermore, genetically engineered animal models, as well as biological and pharmacological studies have suggested that GPR52 has great potential of being a therapeutic psychiatric receptor (Komatsu et al, 2014;Setoh et al, 2014;Nishiyama et al, 2017a,b;Wang et al, 2020).…”
Section: Small-molecule Approaches: Gpr52 Antagonistmentioning
confidence: 99%
“…The first potent GPR52 agonists were reported by Setoh et al, exemplified by 7m (Figure ). Further publications from Setoh et al disclosed other GPR52 agonists such as c17 , and ultimately the molecule FTBMT, which has been thoroughly characterized in vivo , demonstrating both antipsychotic and pro-cognitive effects consistent with the therapeutic hypothesis described above. , Allen and co-workers report PW0787 and associated in vivo antipsychotic activity, and other GPR52 agonists have been published in patents but are not yet disclosed in the scientific literature.…”
mentioning
confidence: 85%